THE INFLUENCE OF DIABETES SELF MANAGEMENT EDUCATION AND SUPPORT FOR SELF EFFICACY AND SELF CARE BEHAVIOUR IN CLIENT WITH TYPE 2 DIABETES MELLITUS - FITRIAH, FITRIAH; HARIS, MUSTOFA; mufarika, mufarika; MEGAWATI, CICILIA DESY; SURYANINGSIH, SURYANINGSIH; RODIYATUN, RODIYATUN (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2020)
Independent diabetes care management is needed for health maintenance. Low self-care is caused by low self-efficacy. The purpose of this study was to analyze the effects of diabetes self-management education and support for self-efficacy and independent behavior in clients with type 2 diabetes mellitus. This observational research used a cross sectional approach. Sample which used clusster sampling method consisted of of 200 people. Independent variable was education and support for independent diabetes management, and dependent variable was self-efficacy and independence. Research analysis techniques used bivariate statistical logistic regression test. The results of Binary Logistic Regression test showed that education and independent management support for diabetes significantly influence self-efficacy with a result of sig 0.001 <α 0.05. Education and support for independent diabetes management significantly influence self-care with sig 0,000 <α 0,05. Self-efficacy affects self-care significantly with sig 0,000 <α 0,05. Self-management education and diabetes support are beneficial for people with type 2 diabetes in increasing self-confidence to control and manage the disease they experience. Keywords: Self-management education, self-efficacy and self-reliance behavior